Integrated Land Use Change Analysis For Soil Ersion Study In Ulu Kinta Catchment [S623. B354 2006 f rb]. - Bawahidi, Khaled Saleh Yaslam (2005)
Ulu Kinta catchment has experienced rapid changes in land use and land cover from 1991 to 2004. These changes have resulted in increased upland erosion and higher concentrations of suspended sediment within the catchment. The goal of this research was to investigate the application of integrated satellite remote sensing and Geographic Information Systems (GIS) techniques to assess land cover changes and the estimation of soil erosion in the water catchment.